Risk and protective factors for drug use and antisocial behavior in Spanish adolescents and young people (2012)
In this study, 2440 adolescents and young people of different localities in the Northwestern Spanish coast participated. The Communities that Care Youth Survey (CTCYS) (Arthur, Hawkins, Pollard, Catalano, & Baglioni, 2002; Glaser, Van Horn, Arthur, Hawkins, & Catalano, 2005) was used to identify drug use and antisocial behavior, and their risk and protective factors in the family, the school, the community and the individual/peers. The objective of the research was to identify the predictive role of age and sex in the drug use and the antisocial behaviour, as well as the identification of common predictive risk and protective factors. Data show that age predicts drug use but not the antisocial behaviour. The common predictive risk factors are school failure, gang involvement, attitudes favourable to and early start of antisocial behaviour. The common protective factors are social skills and moral order beliefs. Results show the relevance of considering risk and protection, confirm the existence of common predictive factors and the reciprocal influence of drug use and antisocial behaviour.